Use of Game-Based Learning Media Education as An Effort to Increase Interest Elementary School Students Learning - Yulia, Nurul Mahruzah; Asna, Umniyah Labibatul; Fahma, Mirda Aini; Reviana, Princess Aualia; Cholili, Fitria Nur; Halimahturrafiah, Nur; Sari, Deva Ratna (JERIT: Journal of Educational Research and Innovation Technology, 2025)
The decline in interest in learning among elementary school students is one of the challenges in the world of education that needs to be addressed immediately. Especially in this digital era, of course we also have to keep up with the times. One innovative solution that can be applied is the use of educational game-based learning media. This study aims to analyze the effectiveness of using educational games in increasing interest in learning among elementary school students. The method used is a literature study and observation of the implementation of game-based learning media in several elementary schools. The results of the study show that educational games can increase student involvement in the learning process, strengthen conceptual understanding, and create a pleasant learning atmosphere. In addition, the use of games can also stimulate students' curiosity and intrinsic motivation. Thus, educational game-based learning media can be an effective strategy in increasing interest in learning among elementary school students. The existence of this learning media is to train students' responses to digital media containing character education in the material being taught. The use of educational game-based learning media is very helpful in learning during the pandemic, because learning with this technology media can be accessed anywhere and anytime, thus providing convenience in helping students learn. The use of educational game-based learning media provides a new and different learning atmosphere.